PENERAPAN DIAGRAM KONTROL D^2 MAHALANOBIS PADA PROSES PRODUKSI MINUMAN KEMASAN RETURNABLE GLASS BOTTLE (Studi Kasus di PT. Coca-cola Bottling Indonesia Central Java) - Muhammad Abid Muhyidin; Diah Safitri; Rita Rahmawati (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
Quality being one of the basic factors in choosing a product consumers. Therefore, an industry or a company should always maintain the quality of their products in order to get loyal customers and are able to survive in the competitive market. Coca-cola Bottling Indonesia Central Java Limited Compay is one of the manufacturing company engaged in the beverage packaging industry and always trying to improve the quality for customer satisfaction. Although it has been to improve the quality, there are still defective product because it does not meet the quality characteristics. Monitoring the result of production process aims to determine whether the process is stable or not. Mahalanobis control chartis one of the control charts that can be used to monitor the production mismatch that is multivariate attributes. By using Mahalanobis control chart, beverage production process of returnable glass bottle (RGB) in Coca-cola Bottling Indonesia Central Java Limited Compay based on the characteristics of disability shows that the results have not yet stable and controllable. This is due to Mahalanobis control chartphase II there are 5 observations of 75 observations or 6.66 % identified uncontrolled observations